Monoecious P. atlantica trees in the Yunt Mountains of Manisa province of Turkey - Kafkas S.; Kaska N.; Cetiner M.S.; Perl-Treves R.; Gucluturk H.; Karaca S. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Pistacia species are dioecious plants. Here we report on a few exceptional monoecious plants of P. atlantica found in the Yunt Mountains of Manisa province of Turkey. Distribution of staminate and pistillate inflorescences on the trees was observed during two years. One of them was fully monoecious. Three trees had several branches with only staminate flowers, while the rest of the branches bore pistillate infloresences. Five trees had staminate inflorescences on several branches that bore also pistillate inflorescences. We tested pollen viability from the monoecious plant with TTC (Triphenyl Tetrazolium Chloride) (73.6-95.1 per cent), and pollen germination, in vitro (33.8-48.3 per cent by the test-tube assay, and 51-64 per cent by the agar-plate assay). Pollen from the fully monoecious tree was used to pollinate P. vera cultivars Ohadi and Vahidi. The hybrids will be tested for sex type, and may be used in the future as a starting point for breeding monoecious cultivated pistachio.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)